Analisis Pembelajaran PAI Bagi Anak Usia Dasar Era Covid-19 di Desa Lawe Dua Kutacane Aceh Tenggara - Muhammad Shaleh Assingkily; Rahmaini Rahmaini; Syafaruddin Syafaruddin; Khamim Zarkasih Putro (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2021)
Abstract: This paper aims to analyze the methods, goals, objectives and materials in Islamic Education learning for elementary age children (MI / SD level) provided by educators during the Covid-19 era in Lawe Dua Village, Kutacane, Aceh Tenggara. The data was collected using a qualitative approach using field study methods (observation, interviews, documentation). Furthermore, the data were analyzed using data reduction techniques, data presentation and drawing conclusions. The validity of the data was tested by using the triangulation technique. The results of this study found that (1) the learning method was carried out by discussion, question and answer, and inviting students to study at the teacher's house; (2) learning objectives so that children continue to receive religious advice through Islamic Education learning; (3) learning objectives are aimed at elementary age children; and (4) the material taught is a combination of the content of the PAI curriculum and local wisdom in the village of Lawe Dua. Abstrak: Tulisan ini bertujuan untuk menganalisa metode, tujuan, sasaran dan materi dalam pembelajaran PAI bagi anak usia dasar (jenjang MI/SD) yang diberikan oleh pendidik pada era covid-19 di Desa Lawe Dua Kutacane Aceh Tenggara. Pemerolehan data dilakukan dengan pendekatan kualitatif menggunakan metode studi lapangan (observasi, wawancara, dokumentasi). Selanjutnya, data dianalisis dengan teknik reduksi data, penyajian data dan penarikan kesimpulan. Keabsahan data diuji dengan teknik triangulasi. Hasil penelitian ini menemukan bahwa (1) metode pembelajaran dilakukan dengan diskusi, tanya jawab, dan mengundang siswa belajar ke rumah guru; (2) tujuan pembelajaran agar anak-anak tetap memperoleh nasihat agama melalui pembelajaran PAI; (3) sasaran pembelajaran ditujukan pada anak usia dasar; dan (4) materi yang diajarkan ialah perpaduan antara muatan kurikulum PAI dan kearifan lokal desa Lawe Dua.